Effects of SGLT2 inhibitors on cardiovascular, renal, and major safety outcomes in heart failure: A meta-analysis of randomized controlled trials. (1st June 2021) - Li, Xuexun; Zhang, Qian; Zhu, Lingming; Wang, Guangqiang; Ge, Peipei; Hu, Aizhen; Sun, Xuerong
Abstract: Aims: Sodium-glucose co-transporter 2 inhibitor (SGLT2i), initially introduced for the treatment of diabetes mellitus (DM), demonstrates cardiovascular and renal benefits in patients with heart failure (HF). We aimed to conduct a meta-analysis of its effects on cardiovascular, renal, and major safety outcomes in HF. Methods and results: PubMed, Embase, Cochrane Library, and Web of Science were searched using the terms of "SGLT2i and HF" or "SGLT2i *". Seven randomized, placebo-controlled trials comprising 14, 113 HF patients (mean age, 66.0 years; female, 27.6%; DM, 58.9%) were included. SGLT2i treatment was associated with lower incidences (compared with placebo) of the composite outcomes of cardiovascular death or hospitalization for HF (HHF) (ratio risk [RR] 0.773; 95% confidence interval [CI], 0.719–0.831; p < 0.001; I 2 = 8.1%), cardiovascular death (RR 0.872; 95% CI, 0.788–0.964; p = 0.008; I 2 = 0.0%), HHF (RR 0.722; 95% CI, 0.657–0.793; p < 0.001; I 2 = 15.4%) and serious decrease in renal function (RR 0.673; 95% CI, 0.549–0.825; p < 0.001; I 2 = 17.7%). SGLT2i treatment was associated with a lower incidence of serious adverse events (SAEs) (RR 0.867; 95% CI, 0.808–0.930; p < 0.001; I 2 = 60.1%), but a higher incidence of volume depletion (RR 1.177; 95% CI, 1.040–1.333; p = 0.010; I 2 = 0.0%). Analysis on patients without DM showed consistent results, except for cardiovascular death. Conclusion: SGLT2i treatment contributed to better cardiovascular and renal outcomes in patients with HF, regardless of the presence or absence of DM. SGLT2i also resulted in a lower incidence of SAEs, although a higher incidence of volume depletion was observed. Highlights: The meta-analysis assessed the effects of SGLT2i on cardiovascular, renal, and major safety outcomes in patients with HF, with the presence or absence of DM. The cardioprotective and renoprotective effects of SGLT2i were observed in patients with HF with low heterogeneity, compared to placebo. For major safety concerns, SGLT2i was associated with a lower incidence of SAEs, but higher incidences of volume depletion, limb amputation, and genital infection. The effects of SGLT2i in HF without DM indicated that the effects of SGLT2i in HF treatment were independent of its antihyperglycemic effects.